UNICEF ESARO guidance on Sign Language for Deaf Children’s Education a nd its Use in Accessible Digital Teaching & Learning Materials | UNICE F Eastern and Southern Africa - Auma Obura, Georgine (UNICEF, 2021)
While we are witnessing a growing awareness among policy makers in the ESA region of the need to make education more inclusive especially fo r children with disabilities, data on children with disabilities, poli cies and funding to support their access to quality education remain m ajor issues and will be bottlenecks to progress towards SDG4. As part of the United Nations Partnership for the Rights of Persons with Disab ilities (UNPRPD) multi-country initiative, “Promoting Inclusive Educat ion through Accessible Digital Textbooks”, UNICEF ESARO wishes to supp ort efforts to improve schooling and learning opportunities for childr en with hearing disabilities by providing guidance on the use of sign languages. The document seeks to improve inclusive education for deaf learners by advancing: The use and official recognition of national si gn languages as the first and most accessible natural languages. Sign language supports deaf children in their linguistic, cognitive, and so cial-emotional development. Consistent use of national sign languages in the development of accessible digital teaching and learning materia ls for deaf children. Although the guidance note focuses primarily on countries in the Eastern and Southern Africa (ESA) region, it can also help inform efforts to develop accessible digital teaching and learni ng materials in other regions.
Keywords: Org:eKitabu